Perbuatan pidana kesusilaan dalam rancangan undang-undang KUHP - Sri Hartini (Jurnal Civics: Media Kajian Kewarganegaraan)
As an independent and sovereignty country, Indonesia should arrange KUHP (Kitab Undang-Undang Hukum Pidana) to avoid loss of criminalities that have been increasing. The renewal of KUHP is very needed because it's not proper with the values of social politic, social philosophy, and social cultural of Indonesia people. It is the basic for sosial, criminal policy, and law enforcement. The urgency of revising of KUHP, specially putting susila crime put in draft criminal code (RUU KUHP) and almost the requirement still be formed widely, not distinguishing between criminal and people who break the rule, but the words "susila Crime” and the newly "statutory rape" and "incest’. According to the renewal, it's needed to direct it into the law development that is democratic and responsive, so that the law's function-that protect the society, can give fairness and as a development instrument will raise suitable with the principle of law country.  Although the draft criminal code (RUU KUHP) still need to be discussed again, remembering the effort to have national KUHP is very urgent, so it's better that draft criminal code (RUU KUHP) is not need more time to be UU, in the other hand, technically we will face difficulties in law enforcement because the representatives and experts are more free to say their thoughts.